New Trends in the Occurrence of Yessotoxins in the Northwestern Adriatic Sea - Silva Rubini; Sabrina Albonetti; Simonetta Menotta; Antonio Cervo; Emanuele Callegari; Monica Cangini; Sonia Dall’Ara; Erika Baldini; Silvia Vertuani; Stefano Manfredini (Toxins, 2021)
Yessotoxins (YTXs) are polycyclic toxic ether compounds produced by phytoplanktonic dinoflagellates which accumulate in filter-feeding organisms. We know that the water temperature in our areas Northwestern Adriatic Sea is optimal for the growth of potentially toxic algae (around 20 °C). In recent years, these temperatures have remained at these levels for longer and longer periods, probably due to global warming, which has led to an excessive increase in toxin levels. The interruption of mussel harvesting caused by algae negatively affects farmers’ revenues and the availability of local fish, causing a major economic loss in Italy’s main shellfish sector. Methods: In the nine years considered, 3359 samples were examined: 1715 marine waters, 73 common clams; 732 mussels; 66 oysters; and 773 veracious clams. Bivalve molluscs were examined for the presence of marine biotoxins, including YTXs, while potentially toxic algae, including those producing YTXs, were searched for and counted in marine waters. The method adopted for the quantification of lipophilic toxins involves the use of an LC-MS/MS system. The enumeration of phytoplankton cells was performed according to the Utermhöl method. Results: Between 2012 and 2020, 706 molluscs were tested for YTXs. In total, 246 samples tested positive, i.e., 34.84%. Of the positive samples, 30 exceeded the legal limit. Conclusion: In this regard, it is essential to develop and activate, as soon as possible, an “early warning” system that allows a better control of the production areas of live bivalve molluscs, thus allowing an optimal management of the plants in these critical situations.